TAREKAT TIJANIYAH (Eksklusifisme dan Eksoterisme Gerakan Tarekat Abad 19) - Zainuddin Hamkah (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
Ahmad Tijani accepted the results seen by the Prophet Muhammad. He got his first education from the age of age and from several other scholars up to 20-21 years. He was interested in Sufism so he made a spiritual journey to Fez Morocco in 1171/1757 to study three tariqats; the Qadiriyah, Nashiriyah and Ahmad bin al-Habib Muhammad tarekat. Then to other cities such as Algeria, Cairo, Mecca and Medina and met with several sheikhs including Sheikh Mahmud al-Karoli and Sheikh Abd. Karim al-Sama (Samaniyah). These sheikhs contributed significantly to al-Tinjani's interactions in the tarekat movement. After Ahmad Tijani's meeting with Sheikh Ahmad bin Abdullah al-Hindi, a Shaykh from India in Mecca at the age of 37, he then went to Medina and met Sheikh Muhammad al-Samman, the founder of the Sammaniyah order. Azyumardi in his research said that with his meeting with Shaykh Samman the topic prompted Ahmad Tijani to prepare his own tarekat separate from other tarekat he attended at the age of 50.